1999
DOI: 10.1021/jf980951k
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Amino Acid Composition and Lysinoalanine Formation in Alkali-Pickled Duck Eggs

Abstract: Duck eggs were pickled in alkali for 20 days to prepare Pidan. The extent of the degradation of compositional amino acids, the formation of lysinoalanine (LAL) in Pidan, and the relationship between the formation of LAL and the racemization values of D-serine and D-aspartic acid in Pidan albumen during the pickling period were investigated. Results showed that the remaining percentages of Cys, Arg, Lys, Ser, and Thr in albumen were much lower than that of the corresponding amino acid in yolk. The formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Remarkable change in pH and free alkalinity was observed in pidan white obtained from both treatments (P <0.05) at the same week 4 of pickling, but pidan white treated with KOH had the lower pH and free alkalinity. The pH of pidan white obtained from KOH treatment after 4 weeks of pickling was 11.16, and a final pH 11.12 of pidan white pickled for 20 days was reported by Chang et al (1999). At an alkaline pH, protein molecules have negative net charges on their surfaces with repulsive forces that increase, decreasing the proteinprotein interactions and increasing the protein-water interactions (Ganasen and Benjakul 2011a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable change in pH and free alkalinity was observed in pidan white obtained from both treatments (P <0.05) at the same week 4 of pickling, but pidan white treated with KOH had the lower pH and free alkalinity. The pH of pidan white obtained from KOH treatment after 4 weeks of pickling was 11.16, and a final pH 11.12 of pidan white pickled for 20 days was reported by Chang et al (1999). At an alkaline pH, protein molecules have negative net charges on their surfaces with repulsive forces that increase, decreasing the proteinprotein interactions and increasing the protein-water interactions (Ganasen and Benjakul 2011a).…”
Section: Resultsmentioning
confidence: 99%
“…Because of its special flavour and taste, pidan is adopted by most Chinese. Generally, pidan can be made of pickling duck or chicken eggs in NaOH solution at ambient temperature for a variable number of days (Chang et al 1972;Su and Lin 1994;Chang et al 1999;Chen and Su 2004;Zhang et al 2011a). During pickling, the alkali penetrates the egg shell and membrane to induce chemical changes of the egg components.…”
Section: Introductionmentioning
confidence: 99%
“…It is indigestible by proteases and its formation implies a loss of lysine in proteins decreasing its nutritional value [6]. This non-protein amino acid has been determined in Pidan, a popular alkali-treated duck egg in Taiwan, and the relationship between the formation of lysinoalanine and the degradation of cysteine, serine, and threonine at various alkalitreating stages was investigated.…”
Section: Aliphatic Amino Acids With Nitrogen In the Side Chainmentioning
confidence: 99%
“…This non-protein amino acid has been determined in Pidan, a popular alkali-treated duck egg in Taiwan, and the relationship between the formation of lysinoalanine and the degradation of cysteine, serine, and threonine at various alkalitreating stages was investigated. A micellar EKC method using 250 mM borate buffer (pH 9.5) with 200 mM SDS and 75 mM b-CD and UV detection at 254 nm was used for the separation of this non-protein amino acid from most protein amino acids (see Table 1) [6]. Results obtained in this work indicated that the formation of lysinoalanine in albumen in the first stage of the pickling process was due to the speedy increase in the pH and the abundant formation of dehydroalanine from cysteine whereas the formation of lysinoalanine in the later pickling period was related much more to the alkali treating time than to the pH factor.…”
Section: Aliphatic Amino Acids With Nitrogen In the Side Chainmentioning
confidence: 99%
See 1 more Smart Citation